2005
DOI: 10.1037/0021-9010.90.6.1280
|View full text |Cite
|
Sign up to set email alerts
|

Performance differences among four organizational commitment profiles.

Abstract: Using cluster analyses, the authors obtained evidence for 4 of these profiles in an energy industry sample (N ϭ 970) and a sample of 345 employed college students. The authors labeled the clusters: allied (i.e., moderate affective and continuance commitment), free agents (moderate continuance commitment and low affective commitment), devoted (high affective and continuance commitment), and complacent (moderate affective and low continuance commitment). Using a subset of the employed student sample (n ϭ 148), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
172
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(189 citation statements)
references
References 36 publications
10
172
1
6
Order By: Relevance
“…Those works that have tried to find if there is a relationship between the performance of a public employee and their organizational commitment, have achieved diverse results. For Seppala et al (2009);Harter et al (2009), Vandenabeele (2009 and Turkyilmaz et al (2011), among others, there is a clear and direct relationship, while for Sinclair et al, (2005) there seems to be no definite evidence that supports this hypothesis.…”
Section: Ijsrmentioning
confidence: 94%
“…Those works that have tried to find if there is a relationship between the performance of a public employee and their organizational commitment, have achieved diverse results. For Seppala et al (2009);Harter et al (2009), Vandenabeele (2009 and Turkyilmaz et al (2011), among others, there is a clear and direct relationship, while for Sinclair et al, (2005) there seems to be no definite evidence that supports this hypothesis.…”
Section: Ijsrmentioning
confidence: 94%
“…Money possesses significant motivating power in as much as it symbolizes intangible goals like security, power, prestige, and a feeling of accomplishment and success. Sinclair et al [17] demonstrates the motivational power of money through the process of job choice. He explains that money has the power to attract, retain, and motivate individuals towards higher performance.…”
Section: Methodsmentioning
confidence: 99%
“…Findings from other studies do reveal that the low productivity associated with Nigeria's Public Servants could be raised if they are provided with some financial incentives [17]. The advancement of an employee from one job position to another job position that has a higher salary range, a higher level job title, and, often, more a higher level job responsibilities, is called a promotion.…”
Section: Provision Of Incentivesmentioning
confidence: 99%
“…Affective commitment, or a person's identification with and involvement in an organization (O'Reilly and Chatman 1986), represents their motivation to "give energy and loyalty to the organization" (Kanter 1968: 499). Research has shown that employees' affective commitment can lead to better performance at the level of the individual (Sinclair et al 2005;Vandenberghe et al 2004) and the organization (Gong et al 2009). Thus, employees often see project failure as a type of negative feedback regarding their work efforts.…”
Section: Negative Emotions and Learning From Project Failurementioning
confidence: 99%
“…Venture capitalists make widespread investments outside domestic markets (Wright et al 2005). It is likely that a new firm will be encouraged to internationalize when the venture capital firm financing it has a high level of international knowledge/expertise.…”
Section: Venture Capital Firmsmentioning
confidence: 99%